Dejavniki gibanja števila redovnic v Sloveniji v 20. stoletju - Bezjak, Sonja (Družboslovne razprave, 2008)
In this work we introduce sociological analysis to discuss the influence of social facts in making a decision to join a convent. We understand catholic religious orders as a legitimate alternative for women who, due to the social system, could not achieve their expected life course. By doing this we upgrade the present theological and historical analysis. We show that in the first half of the 20th century the number of women religious vocations was rapidly growing while in the second half it was rapidly falling. We will try to rethink the demographic imbalance that at the end of the 19th and beginning of the 20th century meant the lack of a male population. At the same time, we connect the growth of womenćs religious orders with specific social circumstances whereby women had little influence and minimal possibilities for their participation in the public sphere.
Keywords: redovnice; redovništvo; woman; ženske; demografija; demography; sociološki vidik; 20.st.; Slovenia; Slovenija